Hemorrhagic transformation after stroke: inter‐ and intrarater agreement. (7th December 2018) - Guenego, A.; Lecler, A.; Raymond, J.; Sabben, C.; Khoury, N.; Premat, K.; Botta, D.; Boisseau, W.; Maïer, B.; Ciccio, G.; Redjem, H.; Smajda, S.; et al.
Abstract : Background and purpose: Hemorrhagic transformation (HT) is a complication of stroke that can occur spontaneously or after treatment. We aimed to assess the inter‐ and intrarater reliability of HT diagnosis. Methods: Studies assessing the reliability of the European Cooperative Acute Stroke Study (ECASS) classification of HT or of the presence (yes/no) of HT were systematically reviewed. A total of 18 raters independently examined 30 post‐thrombectomy computed tomography scans selected from the Aspiration versus STEnt‐Retriever (ASTER) trial. They were asked whether there was HT (yes/no), what the ECASS classification of the particular scan (0/HI1/HI2/PH1/PH2) (HI indicates hemorrhagic infarctions and PH indicates parenchymal hematomas) was and whether they would prescribe an antiplatelet agent if it was otherwise indicated. Agreement was measured with Fleiss' and Cohen's κ statistics. Results: The systematic review yielded four studies involving few (≤3) raters with heterogeneous results. In our 18‐rater study, agreement for the presence of HT was moderate [ κ = 0.55; 95% confidence interval (CI), 0.41–0.68]. Agreement for ECASS classification was only fair for all five categories, but agreement improved to substantial ( κ = 0.72; 95% CI, 0.69–0.75) after dichotomizing the ECASS classification into 0/HI1/HI2/PH1 versus PH2. The inter‐rater agreement for the decision to reintroduce antiplatelet therapy was moderate for all raters, but substantial among vascular neurologists ( κ = 0.70; 95% CI, 0.57–0.84). Conclusion: The ECASS classification may involve too many categories and the diagnosis of HT may not be easily replicable, except in the presence of a large parenchymal hematoma.